VD_FINDINFO HC / 2015 / 304 vom 9. März 2015 - VD Tribunal cantonal (2015)
FRAIS JUDICIAIRES, DÉPENS, RÉPARTITION DES FRAIS, TRANSACTION JUDICIAIRE, RETRAITVOIE DE DROIT, ÉQUITÉ | 106 al. 1 CPC (CH), 107 al. 1 let. e CPC (CH), 107 al. 1 let. f CPC (CH), 241 al. 2 CPC (CH), 242 CPC (CH)